EVALUASI KESELARASAN KEBIJAKAN PEMBANGUAN ELECTRONIC GOVERNMENT ANTARA PEMERINTAH PUSAT, PROVINSI JAWA TENGAH, DAN KABUPATEN/ KOTA ( KOTA TEGAL DAN KABUPATEN BATANG) - Rihandoyo, Rihandoyo; Rahman, Amni Zarkasyi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
E Gov development is directed to develop electronic-based governance in order to improve the quality of public services effectively and efficiently. However, since the launch of Inpres No. 3 Tahun 2003 about policies and development strategies of e gov 10 years ago, the development of e-gov in central and local government has not been in line with expectations. Based on e-gov rank results by United Nation Public Administration Network (UNPAN) put Indonesia in the position 97th in the world, while the results of â€œPemeringkatan e-Government Indonesiaâ€ (PeGI) show that the Central Java Province, Tegal City and Batang Regency showed less of development outcomes. This was due to the absence ofÂ policy harmony between the central and local level to support the development of e gov, there not the institutional care of the synchronous e gov and a strong legal regulation for e gov can regulate development in Indonesia.